(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
Pets are increasingly present in people’s lives and the market for pet products have factors that influence the purchase value. The objective was to analyze the influence of demographic and attitudinal variables of consumers in the Southwest region of the State of Paraná, Brazil in the monthly purchase value of pet products. The design was descriptive, with quantitative survey, using a data collection instrument in the form of a structured questionnaire, validated and adapted in the survey of Sakai (2018). Two groups of variables were used: attitudinal and demographic. The sample was by accessibility, bringing together consumers from a supermarket chain in the Southwest region of the State of Paraná, Brazil, in the online mode. As valid answers for the survey, 466 respondents were considered, according to the identification of consumers in the region established in the database. The survey was applied in August 2019. The influence in the value of monthly spending on pets segment was time that has pets (β = -0,580), number of pets (β = 0,560) and attendance (β = 0,207), corroborating the Hypothesis